2014
DOI: 10.1016/j.psyneuen.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

17β Estradiol increases resilience and improves hippocampal synaptic function in helpless ovariectomized rats

Abstract: Summary Memory impairment is the most commonly reported cognitive symptom associated with major depressive disorder. Decreased hippocampal volume and neurogenesis in depression link hippocampal dysfunction with deficits in memory. Stress decreases hippocampal dendritic spine density and long-term potentiation (LTP) at glutamate synapses, a cellular correlate of learning and memory. However, elevated plasma levels of 17β estradiol (E2) during proestrus increase hippocampal structure and function, directly oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 74 publications
2
30
0
2
Order By: Relevance
“…Our results show a decrease in anxiety for the mid-levels of estrogen (estrus) instead of in the peak in the gonadal hormones (proestrus). This result was surprising since high levels of estrogen appear to be protective in terms of cognition, brain plasticity, and behavior [42,43]. A previous study by Sayin et al [44] found that high levels of estrogen exert an anxiolytic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show a decrease in anxiety for the mid-levels of estrogen (estrus) instead of in the peak in the gonadal hormones (proestrus). This result was surprising since high levels of estrogen appear to be protective in terms of cognition, brain plasticity, and behavior [42,43]. A previous study by Sayin et al [44] found that high levels of estrogen exert an anxiolytic effect.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is further supported by the location of estradiol receptors in the central nervous system; the hippocampus is rich in both estradiol and glucocorticoid receptors, making it an important area of interaction between these hormones. In animal models, estrogen appears to support neuroplasticity at the hippocampus (Gould et al, 1990; Woolley et al, 1990) and to be protective against the negative effects of stress (Bredemann and McMahon, 2014). High estradiol levels during the periovulatory phase of the menstrual cycle may support hippocampal function in part through these protective mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models suggest that female rodents do not gain the same beneficial effect of acute stress on hippocampally-mediated or prefrontal tasks as male animals, and that high estrogen levels enhance the negative effects of stress in these areas(Shansky et al, 2004; Shors and Leuner, 2003). In contrast studies in ovariectomized female rats indicate that estrogen replacement increases resilience to stress in earned helplessness models and support hippocampal plasticity(Bredemann and McMahon, 2014; Smith et al, 2010). The modulation of stress effects on brain activity and function remain unclear and likely depend on the type of stress and measure of function(Shansky, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Como ya hemos mencionado, existen diversos trabajos que reportan los efectos de las hormonas gonadales femeninas en el estado de ánimo. Claros ejemplos son el impacto de la regulación que ejerce el estradiol sobre la actividad cerebral y la plasticidad del mismo, los numerosos estudios en modelos animales que sustentan el efecto del estradiol como antidepresivo en modelos animales con menopausia [72][73][74] y los trabajos sobre población clínica que demuestran los efectos benéficos que los estrógenos tienen sobre el ánimo [75][76][77] . De igual forma, se han encontrado efectos antidepresivos en la dehidroepiandrosterona 78 y la progesterona con su metabolito 5α-reducido, alopregnanolona, que producen efectos antidepresivos 79 , al parecer a través de su unión con el receptor GABA A 80 .…”
Section: La Depresión En La Mujerunclassified